Desain dan Evaluasi Prototipe Jaringan Sensor Nirkabel untuk Monitoring Lahan Persawahan di Kabupaten Gowa - Andi Muhammad Nur Hidayat; A. Zulfan Donangsyah; Aldin Ihsan; Muh. Rihan (System Information and Computer Technology (SYNCTECH), 2026)
Monitoring agricultural land is a crucial element in increasing productivity and food security. Gowa Regency has extensive and scattered rice fields, necessitating an efficient and affordable automated monitoring system. This study designed and evaluated a wireless sensor network (WSN) prototype based on Arduino and XBee modules to monitor land conditions in real time, including temperature, air humidity, and soil moisture. The evaluation included network coverage, connection stability, sensor accuracy, and the system's ability to support environmental data-driven decision-making. The results showed that the prototype was capable of transmitting data in real time with low deviation, demonstrating the potential of WSN as an agricultural monitoring tool in Gowa Regency